Pretreatment of sludge palm oil by ultrasonic energy for biodiesel production - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed (2010)
The reduction of free fatty acids (FFAs) in sludge palm oil (SPO) was measured at different sonication time from 30 to 300 min and the optimum time was determined. It is reasonable to indicate that the pretreatment of SPO by applying ultrasonic energy is related to long sonication time. The results showed that the FFA content of SPO reduced from 24.5% to less than 3 % using molar ratio 10:1, reaction temperature 50o C and 2% wt /wt sulfuric acid to SPO in 300 minutes sonication time.